Business Communication Transformation In The Tourism Msme Sector Of Kota Pari, North Sumatra Through Digital Media Platforms: Challenges And Innovations - Roro Rian Agustin; Yunita Sari Rioni; Dian Septiana Sari; Tengku Noviani Delvira (CERED Indonesia Institute, 2025)
This study examines how micro, small and medium enterprises (MSMEs) in the tourism sector of Kota Pari, North Sumatra, have transformed their business communication through digital media platforms. Using a qualitative case study approach carried out between January and April 2025, primary data were collected through in-depth interviews, field observation, and documentation of social media accounts. The research involved 40 MSME owners and managers engaged in tourism-related businesses (culinary, accommodation, handicrafts, and local guides). Thematic analysis reveals that MSMEs have migrated from oral and offline promotion toward digital channels particularly WhatsApp Business for reservation and customer service, Instagram for visual storytelling, and TikTok for short-form video promotion. Key challenges include limited digital literacy, uneven internet infrastructure, inconsistent content production, and difficulties measuring digital campaign effectiveness. Innovations observed include collaborations with local content creators, community-led digital training programs, usage of low-cost content tools (Canva, CapCut), and peer-sharing initiatives. The study concludes that digital media positively impacts visitor numbers, order frequency, and local brand awareness but requires targeted capacity building, improved infrastructure, and stronger multi-stakeholder support to be sustainable.